2017
DOI: 10.1039/c7py00834a
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable fluorescent polymeric nanoparticles for rewritable fluorescence patterning and intracellular dual-color imaging with AIE-based fluorogens as FRET donors

Abstract: Photoswitchable fluorescent polymeric nanoparticles with AIE-based fluorogens as FRET donors were prepared for rewritable fluorescence patterning and intracellular dual-color imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Photochromism is a result of light-induced reversible color transition of organic, inorganic, biological, and polymeric materials. [57][58][59][60][61][62][63][64][65][66][67][68][69][70] Photochromic reactions are mainly based on cis-trans isomerization, electrocyclization, redox, and light-induced proton transfer mechanisms. The change in the molecular structure before and after light irradiation causes a remarkable variation in the absorption or photoluminescence (PL) spectra.…”
Section: Photochromic Materials For Green Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Photochromism is a result of light-induced reversible color transition of organic, inorganic, biological, and polymeric materials. [57][58][59][60][61][62][63][64][65][66][67][68][69][70] Photochromic reactions are mainly based on cis-trans isomerization, electrocyclization, redox, and light-induced proton transfer mechanisms. The change in the molecular structure before and after light irradiation causes a remarkable variation in the absorption or photoluminescence (PL) spectra.…”
Section: Photochromic Materials For Green Printingmentioning
confidence: 99%
“…Organicinorganic hybrid-binary photochromic systems containing visible light-induced proton releasing agents (nanomaterials, metastable state photoacids [PAH], azobenzene, and phenolsulfophthalein) and proton acceptors (acid dyes or pH indicators) can be used in visible light-excited rewritable paper (VLRP). [62][63][64][65][66][67][68][69][70] PAH is used as a proton releasing agent to make a binary system with an acid dye, such as methyl orange (MO). Figure 2A shows that trans-PAH is transformed to a ring-closed isomer (SP) under UV light and releases protons.…”
Section: Photochromic Materials For Green Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the FA-modified AIE dots with positive charge (+11.2 mV) were synthesized using PEO 113 -b-P(AEFA 2 -co-AEMH 9 -co-St 25 ) and p-DTPACO via a co-precipitation strategy. 45,59 The data based on the transmission electron microscopy (TEM) and dynamic light scattering (DLS) showed that the morphology of FA-modified AIE dots was spherical and the average size was about 40 nm ( Fig. S5A and S6, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…1,4-Phenylenebis((4-(diphenylamino)phen-yl)methanone) (p-DTPACO) and the PEO macro-RAFT agent (PEO 113 -TTC) were prepared via a procedure reported in our previous study. 45,59 MnO 2 nanosheets were synthesized according to the reported methods. 60…”
Section: Materials and Apparatusmentioning
confidence: 99%